Analysis of the potential for developing spiritual tourism attraction (DTW) in Taman Beji Griya Punggul - Made Gede Wahyu Panditha; Nyoman Diah Utari Dewi (Sean Institute, 2024)
A good, competitive and sustainable tourism destination built using local wisdom is the goal of the Badung Regency government. One of the spiritual tourist attractions in Badung Regency is Beji Griya Punggul Park. This park has not been managed and is now an interesting tourist attraction. This research aims to analyze the tourism potential and development strategies of Beji Griya Punggul Park so that it can have a positive impact on the environment, social culture and economy of local communities in Badung Regency. The data analysis used in this research is SWOT analysis. The results of this research identify the spiritual tourism potential of Taman Beji Griya Punggul with 4A components; attraction, access, amenities and ancillary services. The strategy for developing spiritual tourism at Taman Beji Griya Punggul should be to increase digital promotion by using tourism products as additional attractions in increasing the involvement of local communities by collaborating with local tourists or people around tourist locations.